2011
DOI: 10.1021/nn200450c
|View full text |Cite
|
Sign up to set email alerts
|

Block Copolymer Mimetic Self-Assembly of Inorganic Nanoparticles

Abstract: Emerging strategies for assembling inorganic nanoparticles into ensembles with multiscale organization are establishing a new paradigm for the synthesis of devices and functional materials with applications ranging from drug delivery to photonics. In this work, the solution self-assembly of amphiphilic ionic block copolymers into morphologically tunable aggregates provides the inspiration and design strategy for nanoparticle building blocks with the essential chemical and conformational features of ionic block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 41 publications
2
97
1
Order By: Relevance
“…3): BCP-tethered HNPs have been used by multiple researchers to create complex structures such as tubules and vesicles with walls built out of HNPs, [52] as well as lamellae and "segmented worms." [53] Jayaraman and Schweizer used a modified version of the polymer reference interaction site model to investigate structure formation for particles with very low graft densities; 1, 2, 4, and 6 polymers per particle. [54][55][56] Systems with 1 and 2 chains per particle are analogous to di-block and tri-block copolymers, with the nanoparticle forming one of the blocks, and results of these simulations, as well as computational studies by Iacovella, Glotzer, and others show the same micellar, lamellar, and interpenetrating gyroid structures seen in copolymer systems (Fig.…”
Section: Structure Of Hnps and Hnp Assembliesmentioning
confidence: 99%
“…3): BCP-tethered HNPs have been used by multiple researchers to create complex structures such as tubules and vesicles with walls built out of HNPs, [52] as well as lamellae and "segmented worms." [53] Jayaraman and Schweizer used a modified version of the polymer reference interaction site model to investigate structure formation for particles with very low graft densities; 1, 2, 4, and 6 polymers per particle. [54][55][56] Systems with 1 and 2 chains per particle are analogous to di-block and tri-block copolymers, with the nanoparticle forming one of the blocks, and results of these simulations, as well as computational studies by Iacovella, Glotzer, and others show the same micellar, lamellar, and interpenetrating gyroid structures seen in copolymer systems (Fig.…”
Section: Structure Of Hnps and Hnp Assembliesmentioning
confidence: 99%
“…Since GPC results before and after hydrolysis suggest that aggregation numbers for PS/PMMA-CdS and PS/PMAA-CdS should be the same, this agreement between SLS and TEM results supports the conclusion that each core-shell particle ( Figure 4) arises from intraparticle chain rearrangements of a single PS/PMAA-CdS unit upon water addition. We have previously shown that ABNPs exhibit salt-dependent self-assembly characteristics due to the charging of PAA chains in water [17]. Therefore, we investigated the effect of adding salt on the behaviour of PS/PMAA-CdS upon dropwise water addition.…”
Section: Characterization Of Amphiphilic Mixed Brush Quantum Dots (Psmentioning
confidence: 99%
“…When the salt ratio was increased to RNaCl = 3.0, vesicles were also formed ( Figure 5C), although with slightly thicker walls (t = 35 ± 2 nm) than those formed at the lower salt ratio. We have previously shown that ABNPs exhibit salt-dependent self-assembly characteristics due to the charging of PAA chains in water [17]. Therefore, we investigated the effect of adding salt on the behaviour of PS/PMAA-CdS upon dropwise water addition.…”
Section: Characterization Of Amphiphilic Mixed Brush Quantum Dots (Psmentioning
confidence: 99%
See 2 more Smart Citations